(3JSjjQ GdEfJGL hGdYedjGJ(B: (3eONd fXQj hJWHjbj (B/s ((3GdLRGFQ (B: s (3LShQ(B, s, 2013)
(3jMJhj GdcJGH Ydi SJI eMGhQ, GdEWGQ GdYGe dhXjaI GdGfJGL hGdYedjGJ, GJNGP GdbQGQ aj GdGfJGL, cPdc JSjjQ GdeNRhfGJ, eY fXGe JNWjW GdGMJjGLGJ ef GdehGO(B- MRP- (3hJQJjH GdYedjGJ hGdeTGQjY, ceG Cfg GMJhi Ydi HYV GdJeGQjf GdJWHjbjI(B.s
(3eQGLY U(B.203s
Keywords: (3GOGQI GdGfJGLs; (3HMhK GdYedjGJs